Confirmation of a wear‐compensation mechanism in dental roots of ruminants. Issue 2 (15th May 2020) - Ackermans, Nicole L.; Martin, Louise F.; Codron, Daryl; Kircher, Partick R.; Richter, Henning; Clauss, Marcus; Hatt, Jean‐Michel
Abstract: Diet affects many factors of an animal's anatomy, but teeth are a specific focus of dietary research, as their durability lends them to record information on a large variety of scales. Abrasive diets like those of grazing herbivores are known to wear down teeth, but how that wear affects tooth growth and the relations between its different morphological components is rarely investigated. Seven pelleted diets varying in abrasive size and concentration were fed over a 17‐month period to 49 sheep ( Ovis aries ), of which n = 39 qualified for morphology measurements. Using computed tomography, scans of the skulls were made over the course of the experiment, and the impact of diet‐related wear was observed on tooth volume and morphology, including the position of dental burr marks, over time. Digital caliper measurements were applied to 3D renderings of the teeth, and the volume of crown and root segments were investigated separately. We aimed to detect a signal of root growth compensating for wear, and test if this mechanism would be affected by dietary abrasives. Crown‐segment volume loss was correlated to root‐segment volume gain. Height and burr mark measurements indicated a much higher experimental tooth wear than that previously reported for free‐ranging animals. The reason for this is unclear. There was no relationship between tooth height and dentine basin depth. For all parameters, there was no effect of diet; hence, while the measurements corroborate general understanding of tooth wear and compensatory processes, these methods appear not suitable to assess subtle differences between feeding regimes.